2016
DOI: 10.4172/2329-9126.1000249
|View full text |Cite
|
Sign up to set email alerts
|

Early Psychosis in People from Chinese Backgrounds Around the World

Abstract: Studies of the early phase of psychosis reveal that culturally relevant beliefs and practices are related to attitudes toward these symptoms and to help-seeking behaviors. Therefore, a systematic and comprehensive literature review will help to develop more culturally sensitive clinical approaches to serving patients and their family members and lay a foundation for conducting culturally relevant research. Our primary aim was to provide a review of cultural factors of patients with a duration of fewer than 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Cultural differences may also pose an additional challenge for Mainland Chinese immigrants to obtain service. A study has shown that psychosis patients from Mainland China would go to traditional Chinese medicine practitioners or other traditional and religious places for treatment, rather than approaching psychiatric services (Li, Robinson, Min, & Seidman, ). This, together with the difficulty in early detection, led to a long treatment delay among adult psychosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural differences may also pose an additional challenge for Mainland Chinese immigrants to obtain service. A study has shown that psychosis patients from Mainland China would go to traditional Chinese medicine practitioners or other traditional and religious places for treatment, rather than approaching psychiatric services (Li, Robinson, Min, & Seidman, ). This, together with the difficulty in early detection, led to a long treatment delay among adult psychosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with many parts of the world, psychiatric stigma is prevalent in Hong Kong (Chan et al, 2016, 2017; Lee et al, 2016; Mak, Chong, & Wong, 2014; Vogel et al, 2017). Given that the public’s knowledge about mental illness is relatively limited (Li, Robison, Min, Yang, & Seidman, 2016; Tsang, Tam, Chan, & Cheung, 2003), misconceptions can bring about more social distancing. Local findings on psychiatric stigma indicated that 40% of the 1,043 respondents from the general public exhibited negative attitudes toward individuals with mental illness.…”
mentioning
confidence: 99%